Assessing impact of saline intrusion on rice cultivating area in Ke Sach district, Soc Trang province, Vietnam - Thanh Giao Nguyen (Journal of Agriculture and Applied Biology, 2021)
This study was carried out to evaluate the effects of saline intrusion on agricultural activities, thereby proposing adaptation and mitigation measures for local people. Salinity was measured at 15 locations on the main and tributary rivers in Ke Sach district, Soc Trang province, Vietnam from January to September 2020. The method of direct interview with farmers was used to evaluate the knowledge and effects of saline intrusion on agricultural production. Salinity measurement results showed that salinity intrusion occurred and lasted from February to the end of May during the dry season (the Winter-Spring rice crop). During the rainy season (June-September), due to the large amount of water, salinity was only between 0.01 and 0.1‰. However, the research has found significant effects in the Summer-Autumn rice crop due to the accumulation of salinity in the soil from the Winter-Spring rice crop, which reduces the rice yield by 10-30%. The interview results revealed that more than 80% of the farmers were aware of the effects of saline water intrusion. Local authorities also regularly organize seminars to disseminate basic knowledge to the community to minimize the risks and impacts of saltwater intrusion. The proposed temporary solutions include rainwater storage, maintenance of saline prevention sluices, construction of more water regulation canals, financial support, and strengthening of salinity monitoring stations. In order to adapt to the long-term salinity conditions, local authorities need to focus on researching changing cropping patterns, crop structure, using new rice varieties that are able to adapt to drought and salty conditions. Besides, there will be technical assistance, capital for people to adapt well to the saline intrusion situation.